2007
DOI: 10.1161/circulationaha.106.643346
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Improvement in Symptoms, Functioning, and Quality of Life After Peripheral Endovascular Revascularization

Abstract: Background— Patients with peripheral arterial disease often undergo peripheral endovascular revascularization (PER) to alleviate symptoms. Despite the growth of PER, little information exists quantifying the health status benefits after the procedure. Methods and Results— From February 2001 to August 2004, 477 consecutive patients underwent PER for symptomatic peripheral arterial disease. Of these, 300 consented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 18 publications
2
54
1
Order By: Relevance
“…24,25 Evaluation at 12 months demonstrated 13 to 35 point improvement in all Peripheral Artery Questionnaire scales; overall summary score increased 32 points, 4× the threshold considered to be clinically important. 26 …”
Section: Quality Of Lifementioning
confidence: 99%
“…24,25 Evaluation at 12 months demonstrated 13 to 35 point improvement in all Peripheral Artery Questionnaire scales; overall summary score increased 32 points, 4× the threshold considered to be clinically important. 26 …”
Section: Quality Of Lifementioning
confidence: 99%
“…2,4 In addition to their increased cardiovascular risk, PAD patients are known to experience impaired health status due to lower-limb symptoms, sometimes even after receiving a technically successful endovascular revascularization. 5,6 In an era where patient-centered outcomes are becoming an important standard in evaluating treatment options, 7,8 information about subjective health status and its determinants in PAD is relatively under documented as compared with the body of research on health status that is available in other cardiovascular disease groups. This information will be necessary when designing tailor-made disease management programs for PAD patients, as programs developed in cardiac patients are not readily implementable in PAD patients.…”
mentioning
confidence: 99%
“…10 Previous studies also showed that the PAQ had a good test-retest reliability and sensitivity to change. 10,12 In addition, an important issue for the use of disease-specific measures in clinical practice is that they focus on aspects that are relevant for a specific patient population. Our results of the PAQ instrument clearly show the disease-specific nature of this measure, with the PAQ discriminating well between different clinical indices.…”
Section: Discussionmentioning
confidence: 99%
“…10 Although its psychometric properties 10,11 and sensitivity to change after revascularization 12 were adequately documented, there is limited insight into the ability to discriminate between asymptomatic and symptomatic disease and its correlation with traditional clinical indices of disease severity. 10,12 This study was designed to further document its validity by contrasting PAQ scores in patients with asymptomatic and symptomatic disease and by comparing PAQ scores with PADrelated indices, such as walking disease and an established cardiac risk algorithm. More specifically, clinical validity was studied both in this disease-specific instrument and the EQ-5D, a standardized generic instrument applicable in a wide range of medical conditions, containing a 5-dimensional descriptive health status system (EQ-5D) and a visual analogue scale (EQ VAS).…”
mentioning
confidence: 99%